Análise molecular de escaldadura-das-folhas da cana-de-açúcar: otimização dos fatores envolvidos no exame diagnóstico - Teixeira, Otávio Magno (Universidade Federal de São Carlos, 2025)
The use of pre-sprouted seedlings (MPB) has been increasingly adopted to reduce the volume of propagative material in sugarcane planting. The health of these seedlings is essential for the success of the method, especially against systemic bacterial diseases such as ratoon stunting disease and leaf scald. Leaf scald, caused by Xanthomonas albilineans, is one of the most significant diseases for the crop, and its spread occurs primarily through infected propagation materials. Therefore, this work aimed to optimize the routine diagnostic test for detecting X. albilineans in MPBs. In the first assay, five published primer pairs: Ala4/L1, PGBL1/PGBL2, XAF1/XAR1, XaQf/XaQr, and XaABCF3/XaABCR3, were evaluated both under the original conditions described by the authors and under modifications proposed in this study. Additionally, sensitivity in DNA dilutions (sample pool) and detection stability over time (DNA preservation) were evaluated. The tests were performed using pure bacterial culture and total DNA extracted from sugarcane. The results demonstrated that the Ala4/L1 primer pair, with the implemented modifications, was the most effective for diagnosis. The use of composite samples proved viable, while storing DNA at +4°C (refrigeration) was the most efficient preservation method. It was also found that prolonged intervals between DNA extraction and PCR reduce the probability of pathogen detection. Finally, variations in reaction performance were observed between different thermocyclers.
Molecular analysis of leaf scald disease of sugarcane: optimization of factors involved in diagnostic test
Keywords: Xanthomonas albilineans; PCR; Mudas-pré-brotadas (MPB); Detecção; Doença sistêmica; Detection; Pre-sprouted seedling; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; 2. Fome Zero e Agricultura Sustentável